Frequency of ABO blood group system polymorphisms in Plasmodium falciparum malaria patients and blood donors from the Brazilian Amazon region. - Carvalho, D. B.; de Mattos, L. C.; Souza-Neiras, W. C.; Bonini-Domingos, C. R.; Cósimo, A. B.; Storti-Melo, L. M.; Cassiano, G. C.; Couto, A. A.; Cordeiro, A. J.; Rossit, A. R.; Machado, R. L. (Genetics and Molecular Research, 2010)
We investigated the ABO genotypes and heterogeneity of the O alleles in Plasmodium falciparum-infected and non-infected individuals from the Brazilian Amazon region. Sample collection took place from May 2003 to August 2005, from P. falciparum malaria patients from four endemic regions of the Brazilian Amazon. The control group consisted of donors from four blood banks in the same areas. DNA was extracted using the Easy-DNA(TM) extraction kit. ABO genotyping was performed using PCR/RFLP. There was a high frequency of ABO*O01O01. ABO*AO01 was the second most frequent genotype, and the third most frequent genotype was ABO*BO01. There were low frequencies of the ABO*O01O02, ABO*AA, ABO*AB, ABO*BB, and ABO*O02O02 genotypes. We analyzed the alleles of the O phenotype; the O(1variant) allele was the most frequent, both in malaria and non-malaria groups; consequently, the homozygous genotype O(1)(v)O(1)(v) was the most frequently observed. There was no evidence of the homozygous O(2) allele. Significant differences were not detected in the frequency of individuals with the various alleles in the comparison of the malaria patients and the general population (blood donors).
Keywords: adolescent; adult; aged; blood donor; blood group ABO system; Brazil; female; genetic polymorphism; genetics; human; malaria falciparum; male; middle aged; polymerase chain reaction; restriction fragment length polymorphism; ABO Blood-Group System; Adolescent; Adult; Aged; Blood Donors; Female; Humans; Malaria, Falciparum; Male; Middle Aged; Polymerase Chain Reaction; Polymorphism, Genetic; Polymorphism, Restriction Fragment Length; Young Adult